Red Blood Cell Extracellular Vesicle-Based Drug Delivery: Challenges and Opportunities - Chiangjong, Wararat; Netsirisawan, Pukkavadee; Hongeng, Suradej; Chutipongtanate, Somchai (Frontiers in Medicine, 2021)
Recently, red blood cell-derived extracellular vesicles (RBCEVs) have attracted attention for clinical applications because of their safety and biocompatibility. RBCEVs can escape macrophages through the binding of CD47 to inhibitory receptor signal regulatory protein α. Furthermore, genetic materials such as siRNA, miRNA, mRNA, or single-stranded RNA can be encapsulated within RBCEVs and then released into target cells for precise treatment. However, their side effects, half-lives, target cell specificity, and limited large-scale production under good manufacturing practice remain challenging. In this review, we summarized the biogenesis and composition of RBCEVs, discussed the advantages and disadvantages of RBCEVs for drug delivery compared with synthetic nanovesicles and non-red blood cell-derived EVs, and provided perspectives for overcoming current limitations to the use of RBCEVs for clinical applications.